Effect of Vitamin E on Induction of Colonization of Spermatogonial Stem Cells in Vitro - Fateme Salehi; Ali-Asghar Moghaddam; Peyman Rahimi-Feyli (Fasa University of Medical Sciences, 2019)
Background & Objective: Spermatogonial stem cells (SSCs) are undifferentiated germ cells that maintain spermatogenesis during lifetime by balancing between self-renewal and differentiation. The aim of this study was to investigate the effect of different concentrations of vitamin E on spermatogonial stem cells colony formation. Material & Methods: SSCs were isolated from testes of prepubertal lamb by two step enzymatic digestions then purified by differential pllating. The cells were cultured for 10 days in 4 groups. Control group: Basic media (DMEM environment which contains 1% antibiotic and 5% FBS( and treatment groups were treated with 20, 40 and 80 µmol/ml vitamin E added to basic media respectively. Changing of culture media was performed every 72h. Colony number and diameter assay was done by inverted microscope. Identification of SSCs was performed by immunocytochemistry assay against PGP9.5. Results: there were no significant difference in colony number and surface area between treatment groups and between treatment and control groups in days 4, 7and 10. Colony surface area was significantly increased at day 10 compared to day 4 (P<0.05). Conclusion: The results of this study showed vitamin E as an antioxidant doesn't have significant effect on colony induction of SSCs in short term culture in vitro.